A study on location-based mobile map search behavior. Issue 3 (4th July 2016) - Wu, Dan; Qiao, Rui; Li, Yi
Abstract : Purpose: – Mobile users increasingly employ location-based map searches in their daily lives. However, it is still relatively unknown about mobile users' map related search behaviors. The purpose of this paper is to discover the interactions between the users and mobile map search systems, to reveal the shortcomings of existing mobile map search functions, and to propose improvement suggestions. Design/methodology/approach: – Based on a set of controlled user experiments performed on the Baidu mobile phone map, this paper empirically examines users' location-based mobile search behaviors, such as timing, metering, judging and so on. This paper also conducts statistical correlation tests to generate relation tables and diagrams regarding each variable, for example, the relation between the retrieval time and the retrieval steps. Findings: – The results indicate that mobile map users have two important characteristics in their search behaviors: first, mobile map users always follow the single search path. Second, the mobile map search efficiency of users is always low. Research limitations/implications: – The situation simulation testing method is mainly used for the construction of a mobile information search behavior environment, which may make the users be nervous and have some effect on the search efficiency. Practical implications: – Based on the identification of user behaviors, this paper provides suggestions to optimize and improve mobile map search systems. Originality/value: – This paper studies users' mobile map search behavior based on location and explores the features of user behavior from the perspective of human-computer interaction.